A call for aflatoxin control in Asia - Abeera Umar; Hamzah Shahbaz Bhatti; Sabyan Faris Honey (CABI Agriculture and Bioscience)
Abstract Aflatoxins are secondary metabolites, produced by some fungal species of the genus Aspergillus, posing health and economic implications throughout the world. Developing countries in Asia usually have tropical conditions and grow crops susceptible to aflatoxin proliferation. Aflatoxin proliferation is more frequent in tropical regions due to optimal climate conditions required for their production. In general, the developing countries in Asia lack control and regulation strategies, like poor harvesting practices, improper storage and poor transportation conditions resulting in major losses from farm to fork level. A number of aflatoxin positive cases above safe limits have been reported in Asia in various commodities being consumed by the local population. This not only exposes to health issues like growth impairment, immunosuppression, hepatic disorders etc. but also result in heavy economic losses due to trade restrictions. However, rigorous aflatoxin standards mean that many nations would export their best quality food and keep contaminated food domestically, resulting in higher aflatoxin exposure in low or middle-income nations, where hepatitis prevalence is high. Aflatoxin control is needed to protect the Asian population from the risks of aflatoxins and to ensure good quality safe availability of commodities throughout the world by trade. In recent years a number of bioproducts have been introduced successfully worldwide that are safe, efficient and ecofriendly. Such initiatives may be taken in Asia as well to protect our food and feed commodities from aflatoxin contamination.